Spontaneous Omental Infarction: An Unusual Etiology of Abdominal Pain - Allim Khairuddin; Teng, Wei Woon; Nornazirah Azizan; Mohd Firdaus Mohd Hayati; Nik Amin Sahid Nik Lah; Fairrul Masnah @ Kadir (Kathmandu University, 2019)
A 49-year-old lady with previous scars complained of acute abdominal pain for two days. Her right hypochondrium was tender and guarding upon assessment. The laboratory investigations were unremarkable. Due to a diagnostic incongruity, computed tomography of the abdomen was performed showing a suspicious lesion at anterolateral aspect of the ascending colon. Surgical intervention was decided and intraoperative finding was consistent with spontaneous omental infarction. Omentectomy was undertaken and final histology was compatible with the intraoperative diagnosis. Although it is exceptional, omental infarction should be considered as part of the differential diagnoses of right-sided acute abdominal pain with normal laboratory investigations. This case highlights its unexpected discovery and we describe its literature reviews.